HIV risk screening and HIV testing among orphans and vulnerable children in community settings in Tanzania: Acceptability and fidelity to lay-cadre administration of the screening tool. - Michelle M Gill; Ola Jahanpour; Roland van de Ven; Asheri Barankena; Peris Urasa; Gretchen Antelman (PLoS ONE)
Introduction HIV risk screening tool validation studies have not typically included process evaluations to understand tool implementation. The study aim was to assess the fidelity to which an HIV risk screening tool was administered by lay workers and acceptability of delivering home-based screening coupled with HIV testing to beneficiaries in an orphans and vulnerable children (OVC) program. Methods This cross-sectional study was conducted March-April 2019 in two regions of Tanzania. Community case workers (CCW) were observed conducting screenings with OVC 2-19 years and participated in focus group discussions. Research staff used structured observation checklists to capture if screening questions were asked or reworded by CCW. In-depth interviews were conducted with older adolescents and caregivers in their homes following screening and testing. A composite score was developed for the checklist. Qualitative data were thematically analyzed to address screening and testing perceptions and experiences. Results CCW (n = 32) participated in 166 observations. Commonly skipped items were malnutrition (34% of all observed screenings) and sexual activity and pregnancy (20% and 45% of screenings for adolescents only). Items frequently re-worded included child abuse (22%) and malnutrition (15%). CCW had an average composite observation score of 42/50. CCW in focus groups (n = 34) found the screening process acceptable. However, they described rewording some questions viewed as harsh or socially inappropriate to ask. Overall, adolescent beneficiaries (n = 17) and caregivers (n = 25) were satisfied with home-based screening and testing and reported no negative consequences. Learning one's HIV negative status was seen as an opportunity to discuss or recommit to healthy behaviors. While respondents identified multiple benefits of home testing, they noted the potential for privacy breaches in household settings. Conclusions We found sub-optimal fidelity to the administration of the screening tool by CCW in home environments to children and adolescents enrolled in an OVC program. Improvements to questions and their delivery and ongoing mentorship could strengthen tool performance and HIV case finding using a targeted testing approach. Overall, home-based HIV risk screening and testing were acceptable to beneficiaries and CCW, could improve testing uptake, and serve as a platform to promote healthy behaviors for those with limited health system interactions.